Ireland : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2003)
Over the past decade, Ireland has experienced a sustained expansion in output and employment that has raised its per capita income above the ED average. The decline in interest rates, and increasing financial sector competition, rapidly rising disposable income, and high rates of household formation have fuelled a spectacular increase in housing prices. Executive Directors emphasized that wage growth must moderate to preserve external competitiveness and avoid risks to output and employment. Regulatory reform should be oriented firmly toward serving consumer welfare.